Analisis Efektivitas dan Efisiensi Kinerja IPAL Domestik di MGS Menggung PT Pertamina EP Cepu : Bahasa Indonesia - harum, syintia Vatma Kusuma; Kamila, Nadinda Aisyah; Pratama, Rifat Adine (LRI Universitas Muhammadiyah Sorong, 2025)
Domestic wastewater produced by industrial areas, although not directly derived from the production process, still has the potential to cause environmental pollution if not properly treated. This waste generally contains organic pollutants, nutrients, oil and fat, and pathogenic microorganisms. If not properly treated, waste discharge into water bodies can increase BOD, COD, TSS, Oil and Greaset, Ammonia, and Total Coliform levels, which have an impact on water quality degradation. This study aims to evaluate the effectiveness of the performance of the Wastewater Treatment Plant (WWTP) at PT MGS Menggung PT Pertamina EP Cepu by utilizing primary data through field observations and interviews, as well as secondary data in the form of laboratory test results for the period July–December 2024. The evaluation was carried out on six wastewater quality parameters, namely Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Oil and Grease, Ammonia, and Total Coliform. The analysis results show that the average BOD reduction efficiency is 42.8% and COD is 52.31%, which is considered quite effective. Conversely, the reduction efficiency of TSS (38.80%) and Total coliform (39.32%) was still less than optimal. This low efficiency indicates the need for improvements in the sedimentation and disinfection units. Therefore, it is recommended to add a coagulation-flocculation process and optimize the chlorination system to improve WWTP performance so that the treated product meets domestic wastewater quality standards as stipulated in applicable regulations